Children with low birth weight and low gestational age in Oslo, Norway: immigration is not the cause of increasing proportions. Issue 6 (December 1995) - Stoltenberg, C; Magnus, P
Abstract : STUDY OBJECTIVE–To determine the influence of children born to immigrant mothers on the total proportions of low birth weight and preterm deliveries in Oslo and to explain the increases in the proportions of children with low birth weight and low gestational age since 1980-1982. DESIGN–This was a cross sectional study based on Norwegian Medical Birth Registry data and information on mothers' country of birth from the Central Bureau of Statistics. SETTING–Oslo, Norway 1968-91. POPULATION–All births in Oslo between 1968 and 1991 (n = 146 133). MAIN RESULTS–The observed increased proportion of children with low birth weight and low gestational age born after 1980-82 is not the result of an increased proportion of children born to immigrant women. Caesarean section rates have increased dramatically and the higher proportions of children with low birth weight and gestational age may be explained by this. CONCLUSION–Wide use of caesarean section probably results in more children of low birth weight and low gestational age as an iatrogenic effect. The trend in the proportion of children with low birth weight and low gestational age is not correlated to perinatal mortality after 1982. Using proportions of low birth weight and gestational age as indicators of a nation's child health status may therefore be misleading in countries with high rates of caesarean section.